2011
DOI: 10.1002/jssc.201000665
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of anthocyanins in commercial fruit juices by using nano‐liquid chromatography‐electrospray‐mass spectrometry and high‐performance liquid chromatography with UV‐vis detector

Abstract: Nano-LC and conventional HPLC techniques were applied for the analysis of anthocyanins present in commercial fruit juices using a capillary column of 100 μm id and a 2.1 mm id narrow-bore C(18) column. Analytes were detected by UV-Vis at 518 nm and ESI-ion trap MS with HPLC and nano-LC, respectively. Commercial blueberry juice (14 anthocyanins detected) was used to optimize chromatographic separation of analytes and other analysis parameters. Qualitative identification of anthocyanins was performed by comparin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 47 publications
3
36
0
Order By: Relevance
“…The lesser anthocyanins may consist of acetoly, malonoyl and coumaroyl compounds [10]. In this study, 5 coumaroly-glucosides and 5 acetyl-pyranoside anthocyanins were searched for and three minor coumaroyl anthocyanin compounds were identified using MS/MS ions, as confirmed in literature (Table 1) [30,41,43]. The compounds were delphinidin-3-(p-coumaroyl-glucoside), cyanidin-3-(p-coumaroyl-glucoside), and petunidin-3-(p-coumaroyl-glucoside) which, to the best of our knowledge, have not been reported in RAB blueberries (Figure 2).…”
Section: Anthocyaninsmentioning
confidence: 83%
See 1 more Smart Citation
“…The lesser anthocyanins may consist of acetoly, malonoyl and coumaroyl compounds [10]. In this study, 5 coumaroly-glucosides and 5 acetyl-pyranoside anthocyanins were searched for and three minor coumaroyl anthocyanin compounds were identified using MS/MS ions, as confirmed in literature (Table 1) [30,41,43]. The compounds were delphinidin-3-(p-coumaroyl-glucoside), cyanidin-3-(p-coumaroyl-glucoside), and petunidin-3-(p-coumaroyl-glucoside) which, to the best of our knowledge, have not been reported in RAB blueberries (Figure 2).…”
Section: Anthocyaninsmentioning
confidence: 83%
“…A contributing factor is the difference in calculating total anthocyanidins by summation of individual anthocyanidin amounts compared to using the pH differential method which calculates total anthocyanidins as one group of compounds based on UV spectra [59,60]. In general, blueberry results reported from a spectrophotometric method are higher in the same sample than results from methods quantifying the individual anthocyanidins [19,30,61]. Yet, the reverse situation has also been reported [62].…”
Section: Individual Anthocyanidinsmentioning
confidence: 99%
“…Recent research trends have identified some food polyphenols as potential agents of health promotion for their ability to act as antioxidants and free-radical scavengers. A great percentage of articles deals with the analysis of this class of molecules in different food matrices such as fruit juices (Fanali et al, 2011b; …”
Section: Food Analysismentioning
confidence: 99%
“…The analysis of anthocyanins in commercial red fruit juices was assessed by nano-LC by Fanali et al (2011b). Although strong acid conditions (5%, v/v HFo) were used, the 100 mm I.D.…”
Section: Uv (200 Nm)mentioning
confidence: 99%
“…In fact, the use of chromatographic columns with smaller I.D., e.g., from 4.6 mm (classical column) to 100 m m (capillary column) may result in up to 2,000-fold increase in both sensitivity and resolution. This feature, together with the low costs owing to the use of considerably smaller amounts of chiral stationary phase, along with the limited eluent volumes, makes nano-LC a viable alternative to classical ones such as HPLC for the analysis of citrus juice (Fanali et al 2011 ;D'Orazio et al 2007 ) . However, to date, very few papers have been published on the enantioselective separation, identi fi cation, and quanti fi cation carried out by nano-liquid chromatography.…”
Section: Nano-liquid Chromatography (Nano-lc)mentioning
confidence: 99%